2016
DOI: 10.1111/cpr.12270
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Tocotrienol reversal of epithelial‐to‐mesenchymal transition in human breast cancer cells is associated with inhibition of canonical Wnt signalling

Abstract: γ-Tocotrienol suppression of metastatic breast cancer cell proliferation and EMT was associated with suppression of the canonical Wnt/β-catenin signalling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…These activities were observed commonly in the concentration range of 2 to 20 µM. The molecular mechanisms reported for the antiproliferation, proapoptosis, and other anticancer activities of δ‐T3 and γ‐T3, as depicted in Figure 3, involve the inhibitory effects on WNT signaling, 116–120 NF‐κB pathway, 121–123 NOTCH signaling, 123–126 and AKT/mTOR signaling 127,128 ; and/or the activation of STAT3, 129,130 SRC kinase, 130 AMPK, 131 and receptor tyrosine kinases HER3/HER4 132,133 . The inhibition of proliferation and induction apoptosis were also reported to be mediated through tocotrienol‐induced activation of EGR‐1/BAX pathway, 134 upregulation of miR‐34a, 125 miR‐429, 135 p27/CDKN1B, 136 and PPAR‐γ, 137 disruption of lipid raft 132,133 and modification of mitochondria membrane and activation of proapoptosis genes 138–140 .…”
Section: Laboratory Studies On Ve and Cancer Preventionmentioning
confidence: 97%
See 1 more Smart Citation
“…These activities were observed commonly in the concentration range of 2 to 20 µM. The molecular mechanisms reported for the antiproliferation, proapoptosis, and other anticancer activities of δ‐T3 and γ‐T3, as depicted in Figure 3, involve the inhibitory effects on WNT signaling, 116–120 NF‐κB pathway, 121–123 NOTCH signaling, 123–126 and AKT/mTOR signaling 127,128 ; and/or the activation of STAT3, 129,130 SRC kinase, 130 AMPK, 131 and receptor tyrosine kinases HER3/HER4 132,133 . The inhibition of proliferation and induction apoptosis were also reported to be mediated through tocotrienol‐induced activation of EGR‐1/BAX pathway, 134 upregulation of miR‐34a, 125 miR‐429, 135 p27/CDKN1B, 136 and PPAR‐γ, 137 disruption of lipid raft 132,133 and modification of mitochondria membrane and activation of proapoptosis genes 138–140 .…”
Section: Laboratory Studies On Ve and Cancer Preventionmentioning
confidence: 97%
“…In γ‐T3‐treated breast cancer MDA‐MB‐231 cells, cell migration machinery regulators such as RAC1 and WAVE2 signaling were reduced 153 . In addition to the reduced cell migration, γ‐T3‐treated breast cancer MDA‐MB‐231 and T‐47D cells showed epithelial‐mesenchymal transition 119 . Using the same in vitro assays, δ‐T3 was also found to suppress the migration and invasion of non‐small lung cancer cells 124 and colon cancer cells 154 .…”
Section: Laboratory Studies On Ve and Cancer Preventionmentioning
confidence: 98%
“…Both canonical and noncanonical Wnt pathways are involved in EMT of breast stem cells or cancer cells. Wnt ligands (Wnt10b/3) or receptors (FZD7/LRP6) mediate activation of the β‐catenin pathway responsible for EMT induction . In contrast, Wnt5a/5b‐induced EMT is not dependent on β‐catenin, but is involved in FZD2/STAT3 signaling .…”
Section: Wnt Signaling Induces Breast Cancer Cell Epithelial‐mesenchymentioning
confidence: 99%
“…Tocotrienols display potent anti-proliferative, apoptotic and autophagic effects against breast cancer cells. The anti-cancer effect of tocotrienols were found to be associated with suppression in growth factor receptor mitogenic signaling pathway and inhibition of epithelial-to-mesenchymal transition in cancer cell lines (Ahmed et al, 2016). The ability of tocotrienols to inhibit the activation and signaling of a wide variety of membrane bound receptors was recently explained (Alawin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of tocotrienols to inhibit the activation and signaling of a wide variety of membrane bound receptors was recently explained (Alawin et al, 2016). It was found that γ-tocotrienol accumulate in and disrupt the integrity of the lipid raft domain within the plasma membrane of breast cancer cells, and this disruption of lipid raft integrity was associated with a reduction in receptor activation and signaling (Ahmed et al, 2016). Based on the plethora of data on the antitumor activity of the free tocotrienol isomers of vitamin E, it was our hypothesis that substituting the α-tocopherol isomer of vitamin E in TPGS with tocotrienols would have a higher pharmacological or antitumor activity, especially against breast and pancreatic cancer, in addition to serving as a solubilizer.…”
Section: Introductionmentioning
confidence: 99%